2001
DOI: 10.1046/j.1440-1711.2001.01017.x
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of a mouse homologue of the human haematopoietic cell‐specific four‐transmembrane gene HTm4

Abstract: Summary Haematopoietic cell-specific transmembrane-4 (HTm 4 ) is a four-transmembrane protein most closely related to CD20 and the beta subunit of the high affinity receptor for IgE (FcεRIβ). To date, it has only been described in humans, where it is expressed in haematopoietic cells of both myeloid and lymphoid lineages. The function of HTm 4 is unknown; however, as for CD20 and FcεRI-β, it is likely to play a role in signal transduction as part of a multi-subunit cell surface receptor complex. In this study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…Immunoprecipitation studies and western blotting confirm a similar biochemical association between murine HTm4 and KAP protein in a murine leukocyte cell line, P815, suggesting that murine HTm4 plays a similar role in mouse and human leukocytes. Although we have already detected HTm4 expression in primary human mast cells, basophils, eosinophils (Adra et al 1994, Nakajima et al 2004, and also in murine P815, another group did not detect HTm4 mRNA in P815 by PCR (Hulett et al 2001). This could be due to a very low copy number of mRNA that nevertheless corresponds to a very high level or protein.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…Immunoprecipitation studies and western blotting confirm a similar biochemical association between murine HTm4 and KAP protein in a murine leukocyte cell line, P815, suggesting that murine HTm4 plays a similar role in mouse and human leukocytes. Although we have already detected HTm4 expression in primary human mast cells, basophils, eosinophils (Adra et al 1994, Nakajima et al 2004, and also in murine P815, another group did not detect HTm4 mRNA in P815 by PCR (Hulett et al 2001). This could be due to a very low copy number of mRNA that nevertheless corresponds to a very high level or protein.…”
Section: Discussionmentioning
confidence: 70%
“…Murine HTm4 is highly similar to human HTm4 at the DNA and amino acid level, and both proteins display a similar predicted four-transmembrane structure (Figure 1). Comparison to two reported HTm4 cDNA sequences (Hulett et al 2001;) revealed two amino acid sense variants (Ser162Ala and Ser211Thr). CLUSTAL alignment analysis and chromosomal grouping places murine HTm4, like human HTm4, in the MS4 protein superfamily (Hulett et al 2001, Ishibashi et al 2001.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…However, a diverse functionality is beginning to emerge. These functions include roles such as cell surface signaling receptors and intracellular adapter proteins (1)(2)(3)(4)(5)22).…”
mentioning
confidence: 99%